Analyzing the Effect of Learning Styles and Study Habits of Distance Learners on Learning Performances: A Case of an Introductory Programming Course - Çakıroğlu, Ünal (International Review of Research in Open and Distributed Learning, 2014)
This study examined the relationships among learning styles, study habits, and learning performances in an online programming language course. Sixty-two sophomore students who enrolled in an online introductory programming course participated in the study. Kolb’s Learning Style Inventory (LSI) was used to measure the students’ learning styles. Another inventory developed by the researcher was used to determine learners’ study habits. An achievement test was used to put forward their learning performances. As a result, significant relationships between learning styles, study habits, and learning performances were revealed. The results present some ideas about distance learners’ learning styles and study habits for instructors who wish to incorporate synchronous courses and support learners.